2020
DOI: 10.1016/j.msec.2020.111262
|View full text |Cite
|
Sign up to set email alerts
|

A possible use of melatonin in the dental field: Protein adsorption and in vitro cell response on coated titanium

Abstract: Melatonin (MLT) is widely known for regulating the circadian cycles and has been studied for its role in bone regeneration and inflammation. Its application as a coating for dental implants can condition the local microenvironment, affecting protein deposition on its surface and the cellular and tissue response. Using sol-gel coatings as a release vehicle for MLT, the aim of this work was to assess the potential of this molecule in improving the osseointegration and inflammatory responses of a titanium substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Interestingly, Melatonin (MLT), used primarily to regulate the circadian rhythm and its role in bone regeneration and inflammation has been studied. Cerqueira et al (2020) used sol-gel coatings as a release agent for MLT on a titanium substrate, they found that it didn’t improve the ALP activity, but has the potential in the activation and development of pathways. Based on the sol-gel coating, Toirac et al (2020) added two different fungicides (fluconazole and anidulafungin) directly both of them exhibited anti-fungal properties.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Interestingly, Melatonin (MLT), used primarily to regulate the circadian rhythm and its role in bone regeneration and inflammation has been studied. Cerqueira et al (2020) used sol-gel coatings as a release agent for MLT on a titanium substrate, they found that it didn’t improve the ALP activity, but has the potential in the activation and development of pathways. Based on the sol-gel coating, Toirac et al (2020) added two different fungicides (fluconazole and anidulafungin) directly both of them exhibited anti-fungal properties.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…To examine the effects of the Mg-doped materials on gene expression, the MC3T3-E1 cell line was cultured at a density of 1.75 x 10 4 cells cm -2 for 7 and 14 days and RAW264.7 at a density of 30 x 10 4 cells cm -2 for 2 and 4 days. Total RNA was extracted with TRIzol as described in Cerqueira et al 24 . RNA concentration, integrity, and quality were measured using NanoVue® Plus Spectrophotometer (GE Healthcare Life Sciences, Little Chalfont, UK).…”
Section: Relative Gene Expression: Rna Extraction Cdna Synthesis and Qrt-pcrmentioning
confidence: 99%
“…For cDNA synthesis, approximately 1 µg of total RNA was converted into cDNA using PrimeScript RT Reagent Kit (Perfect Real Time; TAKARA Bio Inc., Shiga, Japan). The reaction was carried out in a Prime Thermal Cycler (Techne, Staffordshire, UK) as described in Cerqueira et al 24 . The resulting cDNA was diluted in DNase-free water to a concentration suitable for gene expression evaluation.…”
Section: Relative Gene Expression: Rna Extraction Cdna Synthesis and Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins forming part of this layer initiate and regulate processes such as potential foreign body response, inflammation, coagulation, and fibrinolysis and even bone cell activity in the earlier stages of osteogenesis [ 11 , 14 ]. Consequently, the interaction of the biomaterial when exposed to serum proteins can provide preliminary clues to implant designers as to what compositions are more likely to be rejected/accepted by the host, as previously demonstrated in vitro [ 15 , 16 ] and in vivo [ 14 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%